Associação entre os primeiros mil dias de vida da criança e comportamento de risco às oclusopatias - Traebert, Eliane Silva de Azevedo (2018)
Introduction: The development of the child can be influenced by the first thousand days of life, which comprise the nine months of pregnancy until the end of the second year of life after birth. Malocclusions are changes in the development and growth of maxillary muscles and bones that can alter the dental positioning. Objective: To identify the association between factors of the first thousand days of life and the occurrence of risk behaviors to the malocclusion. Methods: A cross-sectional study involving 664 children born in 2009 living in Palhoça, Brazil. Data collection was performed through interviews with mothers in the homes and oral examinations of children in schools. In the first stage the dependent variables were interruption of exclusive breastfeeding in the fourth and sixth month, use of bottlefeeding, pacifier and digital suction. The independent variables were conditions of the first thousand days. In the second, the dependent variables were the malocclusions. The independent variables were current socio-demographic conditions, breastfeeding practices and sucking habits. Multivariate analyzes were performed using Poisson regression. Results: Maternal schooling, mother and father occupation, teenage pregnancy, attendance at day care, reflux and hospitalization in the first 29 days were associated with breastfeeding practices and nutritive and non-nutritive sucking habits. The current father's occupation, private school type, interruption of exclusive breastfeeding up to the fourth month, and pacifier sucking showed to be associated with molar/canine class II or III relationship, posterior crossbite and anterior open bite. Conclusions: Variables related to the first thousand days of the child's life were associated with the occurrence of risk behaviors for malocclusion. Socioeconomic conditions, breastfeeding practices and sucking habits were shown to be statistically associated with malocclusions.